Early Childhood Education with an Islamic Religious Education Approach in the Era of Community Challenges 5.0: Bibliometrics of Analysis of the term “Islamic Education and Early Childhood Education” - Elihami Elihami (Universitas Muhammadiyah Enrekang, 2021)
This study discusses the Industrial Revolution 4.0. in increasing the use of data and technology for the convenience of human life with an Islamic religious education approach for early childhood at PGRI Standard Corawali, South Sulawesi. The qualitative research method used is through bibliometric analysis which is interpreted as epistemological and religious education towards the era of society 5.0. Data collection techniques used are interviews, observation and documentation. The results showed that the application of inhibiting factors in implementing early childhood education were internal (internal) factors, in the form of awareness and understanding of each individual to carry out religious teachings, and external (external) factors, in the form of guidance and attention from parents. , association in the community around them, and education obtained from school. As for the effort to overcome the obstacle, namely implementing Islamic Religious Education in Early Childhood by providing exemplary and attention and affection for children, so that they can follow those ordered by parents and teachers.